AUTHENTIC PODCAST: A MEDIA ON STUDENTS’ SPEAKING PERFORMANCE - Woro Kusmaryani; Ramli; Reza Nursafitri (LPPM Universitas Muhammadiyah Bulukumba, 2024)
This research investigated whether authentic podcast media affects the speaking performance of tenth-grade students at SMK Kesehatan Kaltara. This research used a quantitative approach and pre-experimental method to implement pre-test, treatment, and post-test. Through random sampling technique the researcher selected nursing b class consisting of 25 students as the sample. The researcher used the normality test, homogeneity test, and paired sample t-test to manage the pre-test and post-test data. This research results indicate an effect of authentic podcast media on students' speaking performance. Data analysis showed that the detected data was normal and homogeneous. The hypothesis test result using the paired sample t-test was smaller than 0.05, showing that Ha was accepted while Ho was rejected. Ha claimed that authentic podcast media affects students' speaking performance at the SMK Kesehatan Kaltara. The influences of using authentic media in speaking contributed to the effect on teachers and students. Teachers used authentic podcast media as additional tools to create new designs in the teaching and learning process. The students changed how they practiced speaking, increasing their fluency, pronunciation, enrich vocabulary, comprehension, and has a positive effect in teaching and learning process.